Central Asia in a reconnecting Eurasia : Tajikistan's evolving foreign economic and security interests - Kuchins, Andrew; Mankoff, Jeffrey, 1977-; Backes, Oliver (CSIS report., 2015)
Central Asia in a Reconnecting Eurasia: Tajikistan's Evolving Foreign Economic and Security Interests, part of a five-volume series, examines the full scope of U.S. national interests in Tajikistan and puts forward the broad outlines of a strategy for U.S. engagement over the coming years.